Life satisfaction - Arie Kapteyn; James P. Smith; Arthur van Soest (Institute for the Study of Labor (IZA), 2009)
We analyze the determinants of global life satisfaction in two countries (The Netherlands and the U.S.), by using both self-reports and responses to a battery of vignette questions. We find global life satisfaction of happiness is well-described by four domains: job or daily activities, social contacts and family, health, and income. Among the four domains, social contacts and family have the highest impact on global life satisfaction, followed by job and daily activities and health. Income has the lowest impact. As in other work, we find that American response styles differ from the Dutch in that Americans are more likely to use the extremes of the scale (either very satisfied or very dissatisfied) than the Dutch, who are more inclined to stay in the middle of the scale. Although for both Americans and the Dutch, income is the least important determinant of global life satisfaction, it is more important in the U.S. than in The Netherlands. Indeed life satisfaction varies substantially more with income in the U.S. than in The Netherlands.
urn:nbn:de:101:1-20090304722
Keywords: I31; J28; D31; 330; Happiness; life satisfaction; vignettes; reporting bias; Lebenszufriedenheit; Meinung; Einkommen; Vergleich; USA; Niederlande